POLYNEURITIS CRANIALIS MULTIPLEX DUE TO MYELOMA RELAPSE. Issue 10 (9th September 2014) - Pegg, Emily; Shukralla, Arif; Mathur, Sachin; Mysore, Divyashree; Kulkarni, Omesh
Abstract : A 48 year old man presented with a sub-acute painless complete right sided ptosis, diplopia, dysphonia, dysphagia and left foot drop. He had a PMH of Multiple Myeloma (MM) in remission after 3 cycles of chemotherapy. On examination he had complete right 3rd, left 12th, bilateral 9th and 10th and cranial nerve palsies along with a left foot drop. A meningeal infiltrative process was suspected. MRI neuraxis revealed subtle leptomeningeal enhancement in the lumbar spine, symmetrical nodular deposits around the jugular foramen bilaterally and enhancement of the right cavernous sinus. Plasma IgG was raised. CSF cytology revealed mitotic plasma cells confirming the clinical suspicion of CNS myelomatosis however a bone marrow biopsy did not show evidence of myeloma relapse. CNS involvement occurs in around 1 % of cases of MM and predicts poor prognosis. This case highlights that a relapse of MM can present in the form of Polyneuritis Cranialis Multiplex without bone marrow evidence of relapse. CNS disease can also be present at initial diagnosis of MM. CNS Myelomatosis should therefore be considered in the differential diagnosis of contiguous or non-contiguous multiple cranial nerve palsies. Investigations should be initiated urgently so that aggressive treatment can start promptly.